2018
DOI: 10.1007/s11255-018-1786-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet (aspirin) therapy as a new option in the treatment of vasculogenic erectile dysfunction: a prospective randomized double-blind placebo-controlled study

Abstract: 100 mg of aspirin administered once a day significantly improved EF in men with VED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 29 publications
0
37
0
4
Order By: Relevance
“…Of the remaining 20 articles, 6 were excluded with different reasons, which included unable to obtain the related data distribution in cases and controls, data not qualified (controls having ED). Finally, the remaining 14 studies (Akbas et al, ; Aldemir et al, ; Aldemir et al, ; Bayraktar & Albayrak, ; Ciftci et al, ; Ciftci et al, ; El Taieb, Hegazy, Maklad, & Khairy, ; Guo et al, ; Guo et al, ; La Vignera et al, ; Otunctemur et al, ; Sambel et al, ; Senturk et al, ; Wang et al, ) were enrolled in our systematic review and meta‐analysis, all of which were identified as case–control studies. No further articles were identified for inclusion through the repeated cited reference screening.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the remaining 20 articles, 6 were excluded with different reasons, which included unable to obtain the related data distribution in cases and controls, data not qualified (controls having ED). Finally, the remaining 14 studies (Akbas et al, ; Aldemir et al, ; Aldemir et al, ; Bayraktar & Albayrak, ; Ciftci et al, ; Ciftci et al, ; El Taieb, Hegazy, Maklad, & Khairy, ; Guo et al, ; Guo et al, ; La Vignera et al, ; Otunctemur et al, ; Sambel et al, ; Senturk et al, ; Wang et al, ) were enrolled in our systematic review and meta‐analysis, all of which were identified as case–control studies. No further articles were identified for inclusion through the repeated cited reference screening.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reporting the PLT levels in ED (1580 subjects) and non‐ED cases (977 subjects) were included in the meta‐analysis (Akbas et al, ; Aldemir et al, ; Aldemir et al, ; Bayraktar & Albayrak, ; Ciftci et al, ; Ciftci et al, ; El Taieb et al, ; Guo et al, ; Guo et al, ; Otunctemur et al, ; Sambel et al, ; Senturk et al, ; Wang et al, ). The pooled SMD indicated that individuals with ED had about 0.215 k/μl higher of PLT levels than those without ED (SMD [95% CI] = 0.215 [0.133–0.297], p = 0.000), with severe heterogeneity existed ( I 2 = 90.1%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…В экспериментальном исследовании противовоспалительный препарат (ацетилсалициловая кислота) оказывал протективный эффект в отношении ЭД у крыс с диабетом [7]. По крайней мере в одном исследовании с участием людей прием препаратов ацетилсалициловой кислоты повышал индекс эректильной функции у мужчин с васкулогенной ЭД [8].…”
Section: научный обзорunclassified